The influence of motivation and competence on the performance of Gapoktan administrators (Case study in BPP Jalaksana District, Kuningan Regency) - Sabila, Difa Madani; Nurlita, Azza; Hakim, Mohammad Yudha Raihan; Aisyah, Siti (International Journal Labs, 2024)
This research aims to determine the magnitude of the influence of motivation and competence both individually and together on the performance of the gapoktan management. The research method used is a quantitative design with descriptive survey techniques to describe and analyze the relationship between the independent variable (motivation and competence) and the bound variable (performance of the management). The data was collected through a questionnaire with a Likert scale to measure respondents' attitudes, opinions, and perceptions. The data analysis includes validity, reliability, normality, and multiple linear regression tests using the SPSS (Statistical Product and Service Solution) program. It was concluded that the variables Motivation (X1) and Competency (X2) together have a significant influence on the Performance of the Management of the Gapoktan. It can be concluded that motivation has a negative influence that is not significant on the performances of the Gapoktans management. Competence has positive and significant influences on the management performance. The results of this study suggest further development of existing research models by linking variables that have already been studied or adding new variables supported by strong theories. The benefits of this research include providing consideration materials for the group administrators in achieving group goals, expanding the researcher's knowledge, and becoming a reference and information for readers for further research.